If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(1-7m)=7(1-3m)-4m
We simplify the equation to the form, which is simple to understand
4(1-7m)=7(1-3m)-4m
Reorder the terms in parentheses
+(+4-28m)=7*(1-3m)-4m
Remove unnecessary parentheses
+4-28m=+7+*(+1-3m+)-4m
Reorder the terms in parentheses
+4-28m=+(+7-21m)-4m
Remove unnecessary parentheses
+4-28m=+7-21m-4m
We move all terms containing m to the left and all other terms to the right.
-28m+21m+4m=+7-4
We simplify left and right side of the equation.
-3m=+3
We divide both sides of the equation by -3 to get m.
m=-1
| 4(2+p)=-(2p+4) | | 4(2+p)=-2(p+4) | | 28=-14n | | 2y-w=x | | -3(6+3x)-8=-8(x+4)+7 | | 49=-7/6x | | 6(-8)= | | 6r-3(6-3r)=4(1-3r)+5 | | 2x+4(x+1)=6(x+2) | | [4y-3x-2][4y+3x+2]= | | 7.2x+6y=-3 | | 3/7=9/n | | 6r-3(6-3r)=4(1-3r+5) | | 2x+4(x+1)=6(x+2)3 | | xsqr+24+xsqr+9=5 | | -1/2(1-3)=1/3(2+1) | | [4y-3x-2y][4y+3x+2]= | | 2/3h-1/3h+11-8 | | m+1/2=8 | | -7(-8n+2)=6(7+8n) | | -7(9a-4b+6c)= | | 8/10-7/10 | | 1/7(a-3)(7a+4)=0 | | (4x^2)(3x^5)= | | -3(3y-10)+2(2y+5)= | | 255=x | | 5m+32=5+8(m+6) | | 2+25y-5y^2=x | | -7(n+6)=3(n+6) | | 4(8+r)=4r+32 | | 35=0.5*7 | | 4(7-7x)=28+6x |